The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/su11010176
|View full text |Cite
|
Sign up to set email alerts
|

Strength Time–Varying and Freeze–Thaw Durability of Sustainable Pervious Concrete Pavement Material Containing Waste Fly Ash

Abstract: Pervious concretes, as sustainable pavement materials, have great advantages in addressing a number of environmental issues. Fly ash, as the industrial by-product waste, is the most commonly used as cement substitute in concrete. The objective of this paper is to study the effects of waste fly ash on properties of pervious concrete. Fly ash was used to replace cement with equivalent volume method at different levels (3%, 6%, 9%, and 12%). The control pervious concrete and fly ash modified pervious concrete wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…With the increase of FA content, the relative dynamic modulus of concrete decreases more greatly. erefore, with the increase of FA content, the salt freeze-thaw resistance of concrete decreases, as reported by Liu et al [35].…”
Section: Evaluation Of Salt Freeze-aw Resistance Of Concretes With Mineralsupporting
confidence: 62%
See 2 more Smart Citations
“…With the increase of FA content, the relative dynamic modulus of concrete decreases more greatly. erefore, with the increase of FA content, the salt freeze-thaw resistance of concrete decreases, as reported by Liu et al [35].…”
Section: Evaluation Of Salt Freeze-aw Resistance Of Concretes With Mineralsupporting
confidence: 62%
“…e mechanical properties of concrete with FA decrease with the increase of FA content, and the decrease range increases with the increase of FA content, which indicates that the secondary hydration degree of FA is low in the 28day strength formation process, which is not enough to improve the strength of concrete [35]. e surface resistivity FA plays the role of microaggregate filling, which can fill the internal defects of concrete [49].…”
Section: Influence Analysis Of Mineral Admixtures and Air Content On Physical And Mechanical Performances Of Concretesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, environment-friendly mineral admixtures for concrete such as fly ash (FA), blast furnace slag (BFS), and silica fume (SF) are strongly recommended to improve salt freeze-thaw resistance because of their contributions to microstructure of concrete [34,35]. Studies on mechanism for salt freeze-thaw have suggested that the invasion of chlorides is responsible for damage from salt crystals, high degree of saturation, and additional hydraulic pressure [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the various environmental conditions of concrete structures, the mechanism of durability deterioration is complex. For instance, carbonization [2], freeze-thaw damage [3][4][5], acid rain [6,7], and ion erosion [8][9][10][11][12] can directly affect the durability of concrete structures. It is necessary to take into account the in-service environmental condition when it comes to the design of new concrete structures and the evaluation and maintenance of existing concrete structures.…”
Section: Introductionmentioning
confidence: 99%